2021
DOI: 10.1038/s41598-021-88598-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-autoimmune diabetes mellitus and the risk of virus infections: a systematic review and meta-analysis of case-control and cohort studies

Abstract: A significant number of studies invoked diabetes as a risk factor for virus infections, but the issue remains controversial. We aimed to examine whether non-autoimmune diabetes mellitus enhances the risk of virus infections compared with the risk in healthy individuals without non-autoimmune diabetes mellitus. In this systematic review and meta-analysis, we assessed case-control and cohort studies on the association between non-autoimmune diabetes and viruses. We searched PubMed, Embase, Cochrane Database of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 97 publications
0
14
0
1
Order By: Relevance
“…A continuous presence of high glucose levels at the peripheral cells may result in several abnormalities that favour both bacterial and viral infection. 89 The exact consequence of hyperglycaemia favouring viral infections such as SARS-CoV-2 infection is discussed in subsequent sections.…”
Section: Okoduwa Sir Et Al Hypothetic Mechanism Of Diabetes Mellitus ...mentioning
confidence: 99%
“…A continuous presence of high glucose levels at the peripheral cells may result in several abnormalities that favour both bacterial and viral infection. 89 The exact consequence of hyperglycaemia favouring viral infections such as SARS-CoV-2 infection is discussed in subsequent sections.…”
Section: Okoduwa Sir Et Al Hypothetic Mechanism Of Diabetes Mellitus ...mentioning
confidence: 99%
“…For example, tuberculosis and type 2 diabetes have been shown to facilitate one another, creating a double burden of two epidemics in several countries [ 14 ]. Links between type 2 diabetes and viral infections have also been demonstrated, generally with the conclusion that diabetes precedes and increases the risk of the viral infection [ 15 ]. A recent meta-analysis estimated increased prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; OR 10.8), hepatitis C (OR 3.6), hepatitis B (OR 1.6) and other viruses among type 2 diabetic patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to human herpesviruses, an increased prevalence of HHV8 among type 2 diabetic patients has been reported in multiple populations [ 15 17 ]. Some cross-sectional studies have also demonstrated an association of HSV1 and CMV serostatus with prevalence of type 2 diabetes [ 15 , 18 20 ], but the results were partly confounded by age and other demographic factors [ 21 ]. Moreover, the cross-sectional nature of these studies means that they cannot demonstrate chronology or causality [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Age, genetic inheritance, environmental variables, lifestyle choices, infections that increase the likelihood of developing T2DM, and others make up the likely etiology. Since viruses and T2D may coexist in an individual through direct or indirect viral-mediated pathways, viral infections appear to be highly related with non-autoimmune diabetes (6)(7) .…”
Section: Introductionmentioning
confidence: 99%